2018
DOI: 10.4314/bcse.v32i1.1
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of antioxidant activity of dried berry infusions with the polyphenols and selected microelements contents

Abstract: ABSTRACT. Antioxidant activity was measured by ferric reducing ability of plasma (FRAP) assay in seven types of infusions prepared from commercial dried berry fruit products: Rosa canina, Vaccinium vitis-idaea, Hiphophae rhamnoides, Hibiscus sabdariffa and three fruit mixtures. Total polyphenols (TP), total anthocyanins and the polyphenolic compounds were determined by HPLC equipped with diode array detector. To estimate the amount of elements released from fruits into the water extracts, levels of Fe, Mn, Zn … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 39 publications
(39 reference statements)
0
6
0
Order By: Relevance
“…Generally, positive correlations were observed between FRAP and Fe, Cu, and Sn content in our research. These results demonstrate that FRAP in fruits has a significant impact on enhancing the extractability of Cu bound with the ability to form chelated metal ions by FRAP and to retain them (37). Antioxidants that react in the FRAP assay are those that can reduce, under the reaction conditions used, the Fe 3+ -TPTZ salt to Fe2+-TPTZ form.…”
Section: Soluble Sugars and Organic Acidmentioning
confidence: 80%
See 1 more Smart Citation
“…Generally, positive correlations were observed between FRAP and Fe, Cu, and Sn content in our research. These results demonstrate that FRAP in fruits has a significant impact on enhancing the extractability of Cu bound with the ability to form chelated metal ions by FRAP and to retain them (37). Antioxidants that react in the FRAP assay are those that can reduce, under the reaction conditions used, the Fe 3+ -TPTZ salt to Fe2+-TPTZ form.…”
Section: Soluble Sugars and Organic Acidmentioning
confidence: 80%
“…The first group included polyphenols, which showed high dependence with antioxidant activity, and inhibitors activities. It is known that the antioxidant activity of fruits is influenced by their phenolic composition [ 37 ]. There was a positive correlation between the DPPH values and polyphenolic compounds content, meaning that the concentration of phenolic compounds may be a good indicator of the reducing capacity in the fruits.…”
Section: Resultsmentioning
confidence: 99%
“…Phytochemical results showed the presence of proanthocyanidins, avonoids, 25 ellagic acid, catechin, gallic acid and caffeic acid as major compounds. 44,45 Ascorbic acid and the phenolic compounds could be participating in the silver and gold nanoparticles formation. It is impossible to describe an exact reaction, but generally, it can be said that hydroxy functional groups containing compounds can reduce metallic cations while forming to ketone groups as R. Kumar published earlier.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, previous study with berries demonstrated moderate positive correlations between AO and Cu (r 2 = 0.439), Zn (r 2 = 0.375) and Mn (r 2 = 0.352), while weak correlation with Fe (r 2 = 0.186) was observed. [42] The prevailing point of view is that concentration of metals in mushrooms is variable since it depends mostly on environmental factors of habitat [43] and must be considered in preparation of food supplements from mushrooms collected in the wild.…”
Section: Macro and Micro Element Contentsmentioning
confidence: 99%